Management and health constraints for small scale dairy production in Africa - Brumby, P.J.; Scholtens, R.G. (1986)
Examines milk imports to Africa in the last decade and the present annual value, major constraints to increased milk output and management problems common to all dairy systems; discusses the complimentarity of crop and livestock production, different approaches to increase milk production, animal health problems, and research activities in milk production.